THE RELATIONSHIP BETWEEN INFORMATION ASYMMETRY, MEDIA EXPOSURE, CAPITAL STRUCTURE, FIRM GROWTH, CSR AND FIRM VALUE - Anggi Sitohang; dedy husrizal syah; Choms Gary Ganda Tua Sibarani (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
The purpose of this investigation is to explore the influence of information asymmetry, media exposure, capital structure, and firm growth on the value of the enterprise and to determine whether CSR acts as a mediator in this connection. The study involved examining 49 mining companies that were listed on the Indonesia Stock Exchange during the 2015-2020 period. The research methodology used purposive sampling to select ten companies that met specific criteria. The research results indicate that CSR was not significantly influenced by information asymmetry, capital structure, and firm growth. However, the research findings suggest that media exposure had a favourable effect on CSR. All four factors - information asymmetry, media exposure, capital structure, and firm growth- had a beneficial influence on firm value. Moreover, the research revealed that CSR did not act as a mediator between information asymmetry, media exposure, capital structure, and growth in firm value.